Pertanggung Jawaban Pidana Terhadap Tindak Pidana Penyeludupan - Azmi Syahputra (Fakultas Hukum Universitas Riau, 2013)
The rapid advances in economics apparently called for the establishment of a system and customs procedures more effective and efficient, and can improve the flow of goods and documents. Smuggling is an issue that is very deep and rooted in Indonesia, it means removing smuggling is a significant problem. Criminal liability against smuggling apply to the offender himself both individuals and legal entities.